Neonatal Diet and Gut Microbiome Development After C-Section During the First Three Months After Birth: A Systematic Review - Pivrncova, Eliska; Kotaskova, Iva; Thon, Vojtech (Frontiers in nutrition, 2022)
BACKGROUND: Cesarean section (C-section) delivery imprints fundamentally on the gut microbiota composition with potential health consequences. With the increasing incidence of C-sections worldwide, there is a need for precise characterization of neonatal gut microbiota to understand how to restore microbial imbalance after C-section. After birth, gut microbiota development is shaped by various factors, especially the infant's diet and antibiotic exposure. Concerning diet, current research has proposed that breastfeeding can restore the characteristic gut microbiome after C-section. OBJECTIVES: In this systematic review, we provide a comprehensive summary of the current literature on the effect of breastfeeding on gut microbiota development after C-section delivery in the first 3 months of life. METHODS: The retrieved data from PubMed, Scopus, and Web of Science were evaluated according to the PICO/PECO strategy. Quality assessment was conducted by the Newcastle-Ottawa Scale. RESULTS: After critical selection, we identified 14 out of 4,628 studies for the evaluation of the impact of the diet after C-section delivery. The results demonstrate consistent evidence that C-section and affiliated intrapartum antibiotic exposure affect Bacteroidetes abundance and the incapacity of breastfeeding to reverse their reduction. Furthermore, exclusive breastfeeding shows a positive effect on Actinobacteria and Bifidobacteria restoration over the 3 months after birth. None of the included studies detected any significant changes in Lactobacillus abundance in breastfed infants after C-section. CONCLUSION: C-section and intrapartum antibiotic exposure influence an infant's gut microbiota by depletion of Bacteroides, regardless of the infant's diet in the first 3 months of life. Even though breastfeeding increases the presence of Bifidobacteria, further research with proper feeding classification is needed to prove the restoration effect on some taxa in infants after C-section. SYSTEMATIC REVIEW REGISTRATION: [www.crd.york.ac.uk/prospero/], identifier [CRD42021287672].
Keywords: breastfeeding; microbiome; delivery mode; bacteria; infant; nutrition; C-section